Ekplorasi Komposisi Choir Nusantara pada Karya Musik Metal Kelompok Djiwoastra - Wahyu Purnomo; Bondan Aji Manggala; Denis Setiaji (Abdi Seni, 2022)
The activity of creating musical works based on Community Service activities with the  title  “Exploration  of  Harmonious  Composition  Techniques  and  Interlocking Vocal Techniques in Metal Musical Works of the Djiwoastra Group” seeks to express musical works that show the marriage between Nusantara aesthetics and Western aesthetics through working on choir vocal compositions. The agreement to collaborate in composing music with an emphasis on the Gregorian choir composite strategy that explores Nusantara vocal forms such as Senggakan and Gerongan (Javanese), as well as the Balinese Kecak vocal interlocking technique is a problem solving point in overcoming the problem of diversity in metal music production techniques required by Djiwoastra music group as partners. The Participation Action Research method is prioritized in this activity. This activity is a vehicle for realizing mutual understanding between the team implementing the activity and the metal music group Djiwoastra, in order to strengthen each other’s potential for the challenges of musical works based on the internalization of diverse experiences. Community service activities that aim to solve problems in balancing the aesthetics of music between West and East have been achieved to some extent by strengthening the trans-medium composite technique of Javanese vocal forms such as Senggakan, Gerongan, and Balinese Kecak which are packaged in a gregorian choral style, which can become a new techniques mastered by partners to develop subsequent works